The Role of Indigenous Mycorrhiza in Combination with Cattle Manure in Improving Maize Yield (Zea Mays L) on Sandy Loam of Northern Lombok, Eastern of Indonesia - Wahyu Astiko; Ika Rochdjatun Sastrahidayat; Syamsuddin Djauhari; Anton Muhibuddin (UNIVERSITY OF LAMPUNG, 2013)
A glass house study was conducted to evaluate the contribution of indigenous arbuscular mycorrhiza fungi (AMF) in improving maize yield grown on sandy loam of Northern Lombok. The package of organic fertilizers treatments were tested including: without inoculation of mycorrhiza, inoculation mycorrhiza and no added inorganic fertilizers, inoculation of mycorrhiza with cattle manure added, inoculation of mycorrhiza with rock phosphate added and inoculation mycorrhiza with inorganic fertilizers. The treatments were arranged using a Completely Randomized Design with four replications. The results of the study show that the inoculation of AMF significantly increased soil concentration of N, available-P, K and organic-C by 37.39%, 60.79%, 66.66% and 110.15% respectively observed at 60 days after sowing (DAS). The similar trend was also found at 100 DAS, where those nutrients increased by 21.48%, 69%, 43.93% and 37.07%, respectively compared to control. The improving of soil fertility status was also reflected by nutrients uptake (i.e. N, P, K, Ca) as well as growth and yield of maize. N, P, K and Ca uptake increased by 1,608%, 1,121%, 533% and 534%, respectively. Roots and top dry biomass at 60 DAS increased by 718.40% and 337.67%, respectively. The trend increased of the biomass was followed by observation at 100 DAS. Yield components including cobs, grain and weight of 100 grains increased by 313.60%, 411.84% and 137.54%, respectively. In addition, the inoculation of AM with F2 contributed significantly to the spore numbers and root infection.[How to Cite : Astiko W, IR Sastrahidayat, S Djauhari, and A Muhibuddin. 2013. The Role of Indigenous Mycorrhiza in Combination with Cattle Manure in Improving Maize Yield (Zea Mays L) on Sandy Loam of Northern Lombok, Eastern of Indonesia. J Trop Soils, 18 (1): 53-58. doi: 10.5400/jts.2013.18.1.53][Permalink/DOI: www.dx.doi.org/10.5400/jts.2013.18.1.53]